TELAAH PESERTA DIDIK DALAM PERSPEKTIF ISLAM - Nadjematul Faizah (ISTIGHNA: Jurnal Pendidikan dan Pemikiran Islam, 2022)
The purpose of Qur'ani education is to cultivate human beings personally and in groups so as to be able to explain their functions as servants of Allah and their caliphs, in order to build this world according to the concept set by Allah Almighty, or in a shorter word and often used by the Qur'an, to be devoted to Him. The target of education is students, therefore educational activities are obliged to provide opportunities to be able to follow the sustainability of all educational activities by not sorting out students based on their level of intelligence and social status background. So that it can produce potential and functional human resources (HR) to raise the level of self-welfare in society. This study uses the method of literature study by making a number of the results of previous researchers' studies as the main data source. The results of this study show that in Arabic literature there are several terms encountered, which are often used to indicate their meaning in learners such as; talib, disciple, tilmidz, al-mudarris, murabba, and thifli. In talking about students, there are two things that are important for educators to pay attention to. First, the nature of students as humans so that the educational process can create humans who can maximize all their potential. Second, the needs of students, which include the need to have life skills and ethics or akhlaq in carrying out the wheel of their lives.